WAYS TO DEVELOP GENDER CULTURE IN ADOLESCENT STUDENTS THROUGH GAMIFICATION - Alibekov Dilshod Islamovich (American Journals Publishing, 2023)
This article describes the ways of developing gender culture in adolescent students by means of gamification. Also, in the article, the teacher presents educational materials with the help of gamification (game-based activity) in forming students' skills of dialogue, discussion, cooperation, creative activity, cross-gender culture, modeling of communication situations. it is emphasized that it is necessary to use the method effectively.
Keywords: Gamification, game, adolescent students, gender culture, teacher activity